Pengaruh Pelaksanaan Program Kesehatan Dan Keselamatan Kerja (K3) Terhadap Kinerja Karyawan Pada PT. Kalisuruh Karsa Mandiri Ngawi - Rosi Dicky Pradipta; Fauzan Almanshur (Universitas Islam Kadiri, 2022)
Performance improvement is the result of well-planned employee activities and coordination to carry out all forms of procedures and a good company is a company that truly maintains the safety and health of its employees by making rules on occupational health and safety that are enforced by all employees and company leaders. A healthy workforce is expected to work productively, increase employee productivity, improve employee performance, and support the company's business success in building and developing its business. This research uses descriptive quantitative method. The object of research at PT. Call for Independent Karsa. The sample used as many as 82 respondents with a sampling technique that is simple random sampling. The data of this research are primary data of questionnaires related to occupational health, work safety, and employee performance. Analysis of the data used in this study is multiple linear regression using SPSS software version 25. The results showed that occupational health had a positive and partially significant effect on employee performance. Work safety has a positive and significant effect partially on employee performance. Occupational health and safety have a positive and significant effect simultaneously on employee performance. Keyword: Health, safety, employee performance